Karakteristik Perkembangan Fisik, Kognitif, Emosi Sosial, dan Moral Pada Anak Usia Sekolah Dasar (7-12 Tahun) - Setiana, Setiana; Eliasa, Eva Imania (Journal Of Human And Education (JAHE), 2024)
The age range of 7 to 12 years in elementary school is a crucial stage of child development, characterized by significant progress in physical, cognitive, social-emotional, and moral aspects. This study aims to identify the characteristics of physical, cognitive, social-emotional, and moral development in elementary school age children (7-12 years) through a systematic literature review. Taking into account the importance of understanding various aspects of child development in the context of education and parenting, this study uses the systematic literature review (SLR) method to collect and analyze relevant studies that have been published between 2020 and 2024. The results showed that children at this age experienced significant physical growth, improved logical and analytical thinking skills, social emotional development involving more complex relationships with peers, and a more mature moral understanding. This finding is expected to provide insight for educators and parents in supporting the optimal development of children.